Digital marketing in Islamic perspective: A literature review - Wahyu Eko Pujianto; Laily Muzdalifah (Universitas Negeri Surabaya, 2022)
Business and trade become an inseparable part of Islamic life. The rapidly growing market in cyberspace is a challenge for business players in the form of goods and services to expand and develop their business strategies, namely in terms of marketing. The purpose of the research in this article is to find out digital marketing from an Islamic perspective. The method used is a literature review, which is a literature search both internationally and nationally conducted using the Google Scholar database, ScienceDirect, ProQuest, JIM (Journal for Islamic Marketing), which is about 40 journal articles and 10 books of full quality and medium that is considered relevant is used in this study. The results show that sharia digital marketing activities must be based on Islamic principles. The implementation of digital marketing in sharia is almost the same as the digital marketing principle, yet the difference is the application of the character of business actors accompanied by sharia marketing ethics following the principles as described in the previous discussion. The steps of sharia digital marketing taken are as follows: Creating a Website and Social Media Account, Branding, Social Media Marketing, Content Marketing, Email Marketing, Video Production, and Segmentation.